Sex differences in vectorcardiogram of African-Americans with and without cardiovascular disease: a cross-sectional study in the Jackson Heart Study cohort. Issue 1 (31st January 2021) - Pollard, James D; Haq, Kazi T; Lutz, Katherine J; Rogovoy, Nichole M; Paternostro, Kevin A; Soliman, Elsayed Z; Maher, Joseph; Lima, Joao AC; Musani, Solomon; Tereshchenko, Larisa G
Abstract : Objectives: We hypothesised that (1) the prevalent cardiovascular disease (CVD) is associated with global electrical heterogeneity (GEH) after adjustment for demographic, anthropometric, socioeconomic and traditional cardiovascular risk factors, (2) there are sex differences in GEH and (3) sex modifies an association of prevalent CVD with GEH. Design: Cross-sectional, cohort study. Setting: Prospective African-American The Jackson Heart Study (JHS) with a nested family cohort in 2000–2004 enrolled residents of the Jackson, Mississippi metropolitan area. Participants: Participants from the JHS with analysable ECGs recorded in 2009–2013 (n=3679; 62±12 y; 36% men; 863 family units). QRS, T and spatial ventricular gradient (SVG) vectors' magnitude and direction, spatial QRS-T angle and sum absolute QRST integral (SAI QRST) were measured. Outcome: Prevalent CVD was defined as the history of (1) coronary heart disease defined as diagnosed/silent myocardial infarction, or (2) revascularisation procedure defined as prior coronary/peripheral arterial revascularisation, or (3) carotid angioplasty/carotid endarterectomy, or (4) stroke. Results: In adjusted mixed linear models, women had a smaller spatial QRS-T angle (−12.2 (95% CI −19.4 to -5.1)°; p=0.001) and SAI QRST (−29.8 (−39.3 to −20.3) mV*ms; p<0.0001) than men, but larger SVG azimuth (+16.2(10.5–21.9)°; p<0.0001), with a significant random effect between families (+20.8 (8.2–33.5)°; p=0.001). SAI QRST was larger in women with CVD as compared with CVD-free women or men (+15.1 (3.8–26.4) mV*ms; p=0.009). Men with CVD had a smaller T area (by 5.1 (95% CI 1.2 to 9.0) mV*ms) and T peak magnitude (by 44 (95%CI 16 to 71) µV) than CVD-free men. T vectors pointed more posteriorly in women as compared with men (peak T azimuth + 17.2(8.9–25.6)°; p<0.0001), with larger sex differences in T azimuth in some families by +26.3(7.4–45.3)°; p=0.006. Conclusions: There are sex differences in the electrical signature of CVD in African-American men and women. There is a significant effect of unmeasured genetic and environmental factors on cardiac repolarisation.